2022
DOI: 10.1039/d2ta03389e
|View full text |Cite
|
Sign up to set email alerts
|

Boosted Zn2+ storage performance of hydrated vanadium oxide by defect and heterostructure

Abstract: The inherent sluggish Zn2+ diffusion and poor electronic conductivity limit the ion intercalation/deintercalation process in aqueous zinc-ion batteries (ZIBs) using an oxide-based cathode. Here, we demonstrated that a heterostructure in...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…These results again verify that the formation of ZVO is the main cause of capacity decay. The satisfactory Zn-storage performance of the prepared amorphous V 2 O 5 @V 2 CT x exceeds that of most recently reported Zn-ion battery cathodes, 21,24–26,41,48–53 and a comparison of the Zn-storage performance of the present work with the recently reported Zn-ion battery cathodes is shown in Table S1 †…”
Section: Resultssupporting
confidence: 50%
“…These results again verify that the formation of ZVO is the main cause of capacity decay. The satisfactory Zn-storage performance of the prepared amorphous V 2 O 5 @V 2 CT x exceeds that of most recently reported Zn-ion battery cathodes, 21,24–26,41,48–53 and a comparison of the Zn-storage performance of the present work with the recently reported Zn-ion battery cathodes is shown in Table S1 †…”
Section: Resultssupporting
confidence: 50%
“…The IR band located at ∼551 and 734 cm −1 originates from the symmetric stretching vibration of O-V-O bonds, 49,50 the band at ∼997 cm −1 mostly corresponds to the stretching vibration of V 5+ ]O bonds, 49,50 and the spectral band located at 1612 cm −1 corresponds to bending vibration of O-H from the intercalated water molecules. 51,52 Thermogravimetric (TG) analysis was carried out for the as-prepared V 10 O 24 $nH 2 O to investigate the corresponding weight loss with respect to temperature. Based on the TG prole (Fig.…”
Section: O 24 $Nh 2 O Materials Characterizationmentioning
confidence: 99%
“…Aqueous zinc-ion battery (AZIB) potentially offers far less risk of fire and is cheaper than the present market-leading yet fire-prone lithium-based batteries. , However, bringing the AZIBs to market soon is less likely achievable, unless important challenges, such as intrinsic sluggish kinetics, severe structural collapse, poor rate performance, and large capacity fade, are specifically tackled. Although some progress has been made so far, the lack of a suitable cathode to tolerate the stable insertion/extraction of Zn 2+ ions is still a challenge. , By far, only a few materials have been utilized as the Zn-intercalation hosts, which include Mn compounds, , V compounds, , Prussian blue analogue (PBA)-based compounds, , and other materials such as organics and Co- and Mo-based compounds. Among these, MnO 2 has been widely studied as the cathode for AZIBs because of its merits like tunable morphologies, low cost, low toxicity, and high density. , Despite these advantages, MnO 2 (α-, β-, γ-, δ-, or amorphous MnO 2 ) generally exhibits high Mn dissolution, low intrinsic electronic conductivity, and large volume expansion caused by the phase transformations upon cycling. Because these drawbacks seriously degrade the overall electrochemical performance (e.g., rapid capacity fading and poor rate capability), great efforts have been devoted to resolving this hurdle. , One emerging way is to deposit MnO 2 on the conductive host, thereby creating new composites such as MnO 2 /CNT­(carbon nanotube), MnO 2 /graphene, , and MnO 2 /carbon. , Indeed, it has been experimentally demonstrated that MnO 2 hosted on porous carbon not only improves the rate performance but also triggers a significant capacity gain during battery cycling. Moreover, it has been reported that the MnO 2 deposited on the host with binary or even multinary additives like Cu, Bi 2 O 3 , and PEDOT could also drastically improve the electrochemical performance of AZIB. In this sense, metal–organic framework (MOF) is an appealing precursor for the preparation of the conductive host for MnO 2 cathode because MOF undergoes carbonization under simple pyrolysis, yielding a composite in the form of conductive graphitic carbon decorated with metal or metal oxide nanoparticles. , MOF-derived carbon materials generally have a 3D poro...…”
Section: Introductionmentioning
confidence: 99%
“…3−5 Although some progress has been made so far, the lack of a suitable cathode to tolerate the stable insertion/extraction of Zn 2+ ions is still a challenge. 6,7 By far, only a few materials have been utilized as the Zn-intercalation hosts, which include Mn compounds, 8,9 V compounds, 10,11 Prussian blue analogue (PBA)-based compounds, 12,13 and other materials such as organics and Co-and Mo-based compounds. 14−16 Among these, MnO 2 has been widely studied as the cathode for AZIBs because of its merits like tunable morphologies, low cost, low toxicity, and high density.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation